How Would Cross-Border Electricity Trade Stimulate Hydropower Development in South Asia? - Timilsina, Govinda R. (World Bank E-Library Archive, 2018)
This study examines the importance of enhancing the cross-border transmission interconnections and regional electricity trade to promote hydropower in the South Asia region and quantifies the potential of hydropower development and trade under alternative scenarios. While South Asia is endowed with large (> 350 gigawatts) hydropower potential, only around 20 percent has been exploited so far. This study shows that development of regional electricity markets through expanded cross-border transmission interconnections and regional electricity trade agreements is needed to benefit the region from the exploitation of the untapped hydropower resources. It also finds that development of hydropower in the region would increase by 2.7 times over the next two decades if the region could facilitate an unconstrained flow of electricity across the borders in South Asia. If a moderate carbon tax is added on top of that, hydropower capacity in 2040 could be more than three times as high as the current level